2020
DOI: 10.1161/circresaha.119.316502
|View full text |Cite
|
Sign up to set email alerts
|

EHD1 Modulates Cx43 Gap Junction Remodeling Associated With Cardiac Diseases

Abstract: Rationale: Efficient communication between heart cells is vital to ensure the anisotropic propagation of electrical impulses, a function mainly accomplished by gap junctions (GJ) composed of Cx43 (connexin 43). Although the molecular mechanisms remain unclear, altered distribution and function of gap junctions have been associated with acute myocardial infarction and heart failure. Objective: A recent proteomic study from our laboratory identified EHD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Cx43 PTMs, particularly phosphorylation of Cx43-S373 and Cx43-S368 and ubiquitination, have been associated with the control of GJ-mediated communication, namely, through modulation of protein–protein interactions associated with intracellular trafficking of Cx43 ( Smyth et al, 2014 ; Martins-Marques et al, 2020 ). Therefore, it is conceivable that phosphorylation and ubiquitination play also a regulatory role on the secretion of EV-Cx43.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cx43 PTMs, particularly phosphorylation of Cx43-S373 and Cx43-S368 and ubiquitination, have been associated with the control of GJ-mediated communication, namely, through modulation of protein–protein interactions associated with intracellular trafficking of Cx43 ( Smyth et al, 2014 ; Martins-Marques et al, 2020 ). Therefore, it is conceivable that phosphorylation and ubiquitination play also a regulatory role on the secretion of EV-Cx43.…”
Section: Resultsmentioning
confidence: 99%
“…WB analysis was performed as previously described ( Martins-Marques et al, 2020 ). For the analysis of CD63, CD81 or CD9, WB was performed in non-reducing conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it was reported that the lateralization of Cx43 in cardiomyocytes subjected to ischemia is mediated by Eps15 homology domain-containing protein 1 (EHD-1) via an endocytic recycling-like mechanism. Furthermore, it has been shown that EHD-1 drives the internalization of Cx43 through a process that requires phosphorylation at serine 368, ubiquitination of Cx43 and interaction with Eps15 [119]. Another relevant cardiac Cx43-interacting protein that was demonstrated to be involved in cardiac I/R injury is the ryanodine receptor 2 (RyR2), which is vital for proper cardiac contractility.…”
Section: Cx43 Protein Partners and Their Role In Cardiac I/r Injury-mmentioning
confidence: 99%